2018
DOI: 10.1166/jnn.2018.14908
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Mesoporous CuCe-Based Ternary Metal Oxide by Nano-Replication and Its Application to Decomposition of Liquid Monopropellant

Abstract: Mesoporous CuCe-based ternary metal oxides were synthesized using KIT-6 as a hard template through a nano-casting method. The mesoporous CuCe-based metal oxides were applied to the catalytic decomposition of the ammonium dinitramide-based liquid monopropellant. The decomposition onset temperature over the meso-CuCe ternary metal oxides was much lower than that over the CuCeOx catalyst prepared by conventional precipitation method. Higher activity of the meso-CuCe ternary metal oxides is attributed to higher su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…ADN decomposition is a violent exothermic reaction, rendering a catalytic bed temperature generally higher than 1200 °C. 113,114 Therefore, the selection of a suitable support for the catalysts is of great signicance for manufacturing a stable catalyst. Al 2 O 3 is widely employed as a support for the decomposition of hydrazine and ADN due to its outstanding mechanical strength.…”
Section: Selection Of Carriers For Adn-based Monopropellant Liquid Pr...mentioning
confidence: 99%
“…ADN decomposition is a violent exothermic reaction, rendering a catalytic bed temperature generally higher than 1200 °C. 113,114 Therefore, the selection of a suitable support for the catalysts is of great signicance for manufacturing a stable catalyst. Al 2 O 3 is widely employed as a support for the decomposition of hydrazine and ADN due to its outstanding mechanical strength.…”
Section: Selection Of Carriers For Adn-based Monopropellant Liquid Pr...mentioning
confidence: 99%
“…In order to apply HAN as an ionic liquid propellant, a high level of stability is required. For this purpose, it must be dissolved in H 2 O [3,25]. Previously, it was reported that there are eight decomposition pathways, expressed here as Equations ( 2)- (9) for the aqueous HAN solution, as follows [26]:…”
Section: Introductionmentioning
confidence: 99%
“…In particular, when Sr or Ba is added into the hexaaluminate structure, it reportedly has high heat resistance even at temperatures of 1200 • C or higher [15,16]. Ir, Pt, Cu, and Rh supported on hexaaluminates were reported as effective catalysts for the decomposition of ADN-and HAN-based liquid monopropellants [17,18]. However, the effects of the synthesis procedure and heat treatment of a hexaaluminate catalyst on the decomposition performance of an ionic liquid propellant remain to be studied.…”
Section: Introductionmentioning
confidence: 99%